Use of HCV-Positive Livers in HCV-Negative Recipients. (3rd July 2020) - Thuluvath, Paul J.; Bruno, David A.; Alukal, Joseph; Satapathy, Sanjaya K.; Thuluvath, Avesh J.; Zhang, Talan
Abstract : INTRODUCTION: There are only limited data on the survival outcomes after transplanting HCV RNA–positive liver into HCV RNA–negative recipients. The objective of our study was to determine whether there were graft and patient survival differences when HCV-negative patients received HCV RNA (nucleic acid amplification testing [NAT] positive)–positive liver grafts. METHODS: We queried the United Network for Organ Sharing data sets from January 2014 to December 2018, and recipients (N = 24, 724) were stratified into 6 groups based on the status of HCV antibody and RNA of recipients and donors. The Cox proportional hazard regression was used to estimate the relationship between groups and 1-year post-LT graft or patient survival. RESULTS: During the study period, 1, 358 recipients received NAT-positive liver grafts. Two hundred ten of the recipients were HCV negative. During the same period, 707 HCV antibody–positive but NAT-negative grafts were transplanted into 516 HCV-positive and 191 HCV-negative recipients. There were no differences in survival in HCV-positive recipients whether they received NAT-positive grafts (n = 1, 148) or HCV antibody–negative/NAT-negative grafts (n = 6, 321). Recipients of grafts from HCV antibody–positive/NAT-negative donors had similar survival whether recipients were HCV-negative patients (n = 191) or HCV-positive patients (n = 516), and their survival probabilities were similar to those of HCV-negative recipients (n = 6, 321) receiving grafts from HCV antibody–negative/NAT-negative donors. Patient survival was lower ( P = 0.049) when HCV-negative recipients (n = 210) received NAT-positive grafts compared with HCV-positive patients (n = 1, 148) receiving NAT-positive grafts; however, when adjusted for recipient and donor characteristics, the difference was not significant. DISCUSSION: HCV-negative recipients receiving HCV-positive liver grafts (NAT positive) have excellent 1-year survival outcomes.